Budgeting in an open system - Wojciech A. Nowak (Revista Contabilidade & Finanças, 2004)
Budgeting is broadly used as a tool for organizational management. And this is a reason for continuous looking for budgeting essence. In the paper the systems approach is applied to investigating the nature of budgeting. The systemic aspect of an organization and the systems approach to management were taken into account. Budgeting is seen as the process of prediction and communication of systemic attributes of an organization. It seems that the results reached point to the systems approach as a basis for general theory of both budgeting and accounting. O orçamento é amplamente utilizado como uma ferramenta de gestão organizacional. Este é um dos motivos pela busca permanente da essência do orçamento. Neste estudo, a abordagem sistêmica é aplicada à análise da natureza do orçamento. Foram considerados o aspecto sistêmico de uma organização e a abordagem sistêmica à gestão. O orçamento é entendido como o processo de previsão e comunicação de atributos sistêmico de uma organização. Parece que os resultados alcançados indicam a abordagem sistêmica como base de uma teoria geral de orçamento e contabilidade.